Whole-Genome Sequences and Comparative Genomics of Salmonella enterica Serovar Typhi Isolates from Patients with Fatal and Nonfatal Typhoid Fever in Papua New Guinea - Baddam, Ramani; Thong, Kwai Lin; Avasthi, Tiruvayipati Suma; Shaik, Sabiha; Yap, Kien Pong; Teh, Cindy Shuan Ju; Chai, Lay Ching; Kumarasamy, Narender; Ahmed, Niyaz (American Society for Microbiology, 2012)
Many of the developing countries of the Southeast Asian region are significantly affected by endemic typhoid fever, possibly as a result of marginal living standards. It is an important public health problem in countries such as Papua New Guinea, which is geographically close to some of the foci of endemicity in Asia. The severity of the disease varies in different regions, and this may be attributable to genetic diversity among the native strains. Genome sequence data on strains from different countries are needed to clearly understand their genetic makeup and virulence potential. We describe the genomes of two Salmonella Typhi isolates from patients with fatal and nonfatal cases of typhoid fever in Papua New Guinea. We discuss in brief the underlying sequencing methodology, assembly, genome statistics, and important features of the two draft genomes, which form an essential step in our functional molecular infection epidemiology program centering on typhoid fever. The comparative genomics of these and other isolates would enable us to identify genetic rearrangements and mechanisms responsible for endemicity and the differential severity of pathogenic salmonellae in Papua New Guinea and elsewhere.